(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Tourism in Tanzania remains heavily dependent on wildlife attractions, while alternative niches such as gastronomy tourism receive limited attention. This paper examines poultry farming as a potential driver of gastronomy tourism through a farm-to-table lens. The objectives are to assess the cultural and economic significance of poultry in Tanzania’s food systems and tourism value chains; analyze how poultry-based cuisines contribute to cultural tourism; identify opportunities for integrating women and youth farmers into gastronomy initiatives and propose a conceptual farm-to-table framework. The study employs a desk-based scoping review of peer-reviewed literature, national policies, and international reports (2015–2025), drawing on poultry value-chain analyses and gastronomy tourism research from Tanzania, Africa, and beyond. Findings reveal no prior research directly linking poultry farming with gastronomy tourism, underscoring the novelty of this inquiry. Poultry contributes significantly to household protein supply, with women and youth comprising over 80% of smallholder keepers. Iconic dishes such as mchemsho wa kuku, shawarma, changamoto, and kuku choma represent valuable branding assets. Key challenges include high feed costs, biosecurity risks, and weak institutional coordination. Policy recommendations emphasize farmer-hospitality linkages, regional poultry cuisine branding, and targeted capacity building aligned with Tanzania’s Tourism Master Plan.